Stress and coping strategies among undergraduate nursing students: A descriptive assessment from Western Rajasthan - Mamta Nebhinani; Ashok Kumar; Aashish Parihar; Raj Rani (Wolters Kluwer Medknow Publications, 2020)
Background: Nursing is a very challenging profession, which requires very stringent training since initial years of nursing education. Throughout the training period, students are exposed to various stressful situations. Inability to cope up with varied stressors may lead to psychological distress and impede students' pursuits of nursing career. Objectives: The aim of the present study is to assess stress and coping strategies among nursing students of Western Rajasthan. Materials and Methods: Two hundred and twenty-one undergraduate nursing students were recruited for the study through total enumeration. Standardized Student Nurse Stress Index and brief cope scale were used to assess stress and coping strategies. Results: Nearly 82.4% of the students reported moderate level of stress. Interface worries (mean score 17.88 ± 4.9) and academic load (mean score 17.6 ± 4.78) were the major source of perceived stress. Students considered attitude of other professionals toward nursing, lack of free time, and fear of examination as most likely reasons of their distress. Active coping was the most commonly used coping strategies. Level of stress was found to have significant association with the interest of students in nursing. Conclusions: Interface worries and academic-related concerns emerged as major source of stress. A positive trend was evident in the use of adaptive coping strategies over succumbing meekly. However, there is a great need to plan and implement stress management programs so that these budding health professionals could be better equipped and trained to face various challenges of the profession.